"Thereness": Implications of Heidegger's "presence" for Māori. (March 2015) - Mika, Carl Te Hira
For Māori, the philosophical consequences of colonization are a hugely important issue, due to both the subtlety and the omnipresence of Western metaphysics. In this article I refer to the "metaphysics of presence" through one major Western thinker—Martin Heidegger—who identified "presence" as a problem for the West. He proposes that the metaphysics of presence underpins every perception in the West and that it is the fundamental mistake of philosophers since Plato but becoming ascendant with Aristotle. I identify the points of relevance within their claims and refer them to a Māori understanding of absence. I also consider the more affective nature of Western presence, which Heidegger refers to but which must be theorized by Māori. In the first instance I place particular emphasis on the ironies implicit in writing about metaphysics for the Māori writer in the academy and for the things being represented in that writing. Finally, the metaphysics of presence opens up possibilities for its own instability; this Heideggerean "saving power" is discussed in Māori terms.